Relationship of the erythrocyte sedimentation rate to acute phase proteins in polymyalgia rheumatica and giant cell arteritis. Issue 5 (October 1981) - Park, J. R.; Jones, J. G.; Hazleman, B. L.
Abstract : We have compared the erythrocyte sedimentation rate (ESR) with other acute phase proteins (C-reactive protein (CRP), α1 antitrypsin, orosomucoid, and haptoglobin) in 108 patients with polymyalgia rheumatica and/or giant cell arteritis. There was good correlation between CRP and ESR, but the ESR was also found to have the highest correlation with disease activity. The additional measurement of CRP or other acute phase proteins may be of value in a minority of cases.